SOSIALISASI HUKUM PERJANJIAN TERAPEUTIK DUSUN BENTENNGE DESA BIRORO KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - Jusri Mudjrimin; Syahrul Yadi; Jusmianti; Kusnadi (INKAMKU : Integrasi Akademisi dan Masyarakat yang Berkualitas, 2025)
Some members of the community still lack understanding regarding agreements between healthcare professionals and patients, which can lead to violations and legal disputes that may harm both parties. Therefore, understanding the law of therapeutic agreements is needed. This Community Service activity was carried out through interactive lectures, discussions, question-and-answer sessions, and simple quizzes. The material presented included: therapeutic agreements; types of therapeutic agreements; important elements within therapeutic agreements; the legal principles underlying therapeutic legal agreements; legal agreements referring to the provisions in Article 1320 of the Civil Code; forms of communication between healthcare professionals, as a form of professional communication between healthcare providers and patients; elements of therapeutic transactions that must exist in the interaction process between healthcare professionals (doctors, nurses, or other health workers) and patients; the requirements for a valid therapeutic transaction referring to the provisions that must be met so that the relationship between healthcare workers and patients is considered valid both legally and ethically; the parties involved; termination of therapeutic transactions or relationships. Essentially, this socialization activity was expected to receive a good response from the people of Dusun Bentennge, Biroro Village, East Sinjai District, Sinjai Regency. However, participation was still limited due to routine activities in the village. Therefore, it is hoped that the information received from the socialization can be conveyed to the surrounding community